Pengaruh Lama Perendaman Dalam Natrium Metabisulfit Terhadap Karakteristik Fisikokimia Tepung Kernel Biji Mangga Arum Manis (Mangifera indica L.) - Utpati, I Gusti Agung Veto; Sri Wiadnyani, Anak Agung Istri; Putra, I Nengah Kencana (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPA, 2025)
The potential of carbohydrate sources, such as mango seeds, has not been widely explored. The high production level of Arum Manis mangoes results in an increased amount of waste in the form of mango seeds. The waste from Arum Manis mango seeds contains carbohydrates that can be turned into flour; however, it faces the problem of browning. One solution is to soak the seeds in sodium metabisulfite. This research sought to identify the impact of varying soaking durations in sodium metabisulfite on the physicochemical properties of Arum Manis mango seed kernel flour and to establish the optimal soaking time to obtain the flour's best characteristics. The experimental design used in this study was a Completely Randomized Design with one treatment factor, which was the soaking time in 1000 ppm sodium metabisulfite, with five levels: 0, 30, 60, 90, 120 minutes. Every treatment was conducted three times, leading to a total of 15 experimental units. The collected data were analyzed through analysis of variance, and any observed effects on the parameters were further examined using Duncan's Multiple Range Test. The results of the study showed that the soaking time in sodium metabisulfite had a significant effect on starch content, total phenol content, and color. The best characteristics were obtained with a soaking time of 120 minutes, resulting in moisture content of 7.05%, total phenol content of 42.92 mg/g, starch content of 40.88%, pH of 5.52, fat content of 15.44%, protein content of 6.83%, ash content of 1.84%, carbohydrate content of 68.83%, crude fiber content of 8.87%, L* value of 90.67, a* value of -1.3, and b* value of 3, interpreted as pale yellowish-white. Keywords: arum manis mango, waste, sodium metabisulfite, kernel seed flour